Relationship between family functioning and self-transcendence in patients with breast cancer: A network analysis - He, Chunyan; Yang, Tianqi; He, Yang; Guo, Sijin; Lin, Yawei; Wu, Chao; Gao, Li; Liu, Xufeng; Wu, Shengjun; Cao, Baohua (Frontiers in Public Health, 2022)
Background For patients with breast cancer, family functioning is an important factor affecting self-transcendence, which is a key source of happiness. However, network analysis studies of family functioning and self-transcendence are lacking, particularly among patients with breast cancer. Purpose The present study investigated the network structure of family functioning and self-transcendence in patients with breast cancer and aimed to identify bridge items to provide some theoretical support for the improvement and intervention of self-transcendence in patients with breast cancer. Methods A total of 294 patients with breast cancer were enrolled in our study. Self-transcendence was evaluated with the Self-Transcendence Scale. Family functioning was evaluated with the Family Adaptation, Participation, Growth, Affection, Resolution (APGAR) Scale. Network analyses were used for the statistical analysis. Results In the network of family functioning and self-transcendence in patients with breast cancer, there were 22 edges across communities, of which the 5 strongest edges connected to the 5 dimensions of family functioning are “Adaptation” with “Enjoyment of hobbies”, “Participation” with “Life enjoyment”, “Growth” with “Acceptance of bodily changes”, “Affection” with “Life enjoyment”, “Resolution” with “Help acceptance”. “Adaptation” had the highest bridge expected influence value (0.30) in the family functioning community, while “Life enjoyment” had the highest bridge expected influence value (0.27) in the self-transcendence community. Conclusion Complex patterns of associations existed in the fine-grained relationship between family functioning and self-transcendence in patients with breast cancer. From the perspective of network analysis, the “Adaptation” aspect of family functioning and the “Life enjoyment” aspect of self-transcendence may be the best targets for improving self-transcendence. These results have important implications to clinical practice, which provided potential targets for interventions to improve self-transcendence from the perspective of family functioning.